2,2 `-(Disulfanediyl)dibenzoic acid-N,N `-bis(4-pyridylmethyl)ethanedithioamide (1/1) - Arman, H.D.; Miller, T.; Poplaukhin, P.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
The asymmetric unit of the title co-crystal, C(14)H(14)N(4)S(2)center dot C(14)H(10)O(4)S(2), comprises a twisted 2,2'-(disulfanediyl)dibenzoic acid molecule [ dihedral angle between the benzene rings = 83.53 (14)degrees] and a U-shaped molecule of N,N'-bis(4-pyridylmethyl) ethanedithioamide in which intramolecular N-H center dot center dot center dot S hydrogen bonds are observed. Two molecules of each form a centrosymmetric ring, with an extended chair conformation, mediated by carboxyl-pyridine O-H center dot center dot center dot N hydrogen bonds between the carboxylic acid groups of two 2,2'-(disulfanediyl) dibenzoic acid molecules and pyridine-N atoms of two N, N'-bis(4-pyridylmethyl) ethanedithioamide molecules. The tetrameric aggregates are linked into a supramolecular chain along the b axis via amide-carbonyl N-H center dot center dot center dot O hydrogen bonds.